Expression of CDK1(Tyr15), pCDK1(Thr161), Cyclin B1 (Total) and pCyclin B1(Ser126) in Vulvar Squamous Cell Carcinoma and Their Relations with Clinicopatological Features and Prognosis - Wang, Zhihui (PLoS One, 2015)
Cyclin B1-CDK1 complex plays an important role in the regulation of cell cycle. Activation of Cyclin B1 and CDK1 and the formation of the complex in G2/M are under multiple regulations involving many regulators such as isoforms of 14-3-3 and CDC25 and Wee1. Abnormal expression of Cyclin B1 and CDK1 has been detected in various tumors. However, to our knowledge no previous study has investigated Cyclin B1 and CDK1 in vulvar cancer. Therefore, we evaluated the statuses of CDK1(Tyr15), pCDK1(Thr161), Cyclin B1 (total) and pCyclin B1(Ser126) in 297 cases of vulvar squamous cell carcinomas by immunohistochemistry. Statistical analyses were performed to explore their clinicopathological and prognostic values. In at least 25% of tumor cases high expression of CDK1(Tyr15), pCDK1(Thr161), Cyclin B1 (total) and pCyclin B1(Ser126) was observed, compared to the low levels in normal vulvar squamous epithelium. Elevated levels of CDK1(Tyr15), pCDK1(Thr161), Cyclin B1 (total) and pCyclin B1(Ser126) were correlated with advanced tumor behaviors and aggressive features. Although CDK1(Tyr15), pCDK1(Thr161), Cyclin B1 (total) and pCyclin B1(Ser126) could not be identified as prognostic factors, combinations of (pCDK1(Thr161 C+N) + 14-3-3σ(N)), (pCDK1(Thr161 C+N) + 14-3-3η(C)), (pCDK1(Thr161 C+N) + Wee1(C)) and (pCDK1(Thr161 C+N) + 14-3-3σ(N) + 14-3-3η(C) + Wee1(C)) were correlated with disease-specific survival (p = 0.036, p = 0.029, p = 0.042 and p = 0.007, respectively) in univariate analysis. The independent prognostic significance of (pCDK1(Thr161 C+N) + 14-3-3σ(N) + 14-3-3η(C) + Wee1(C)) was confirmed by multivariate analysis. In conclusion, CDK1(Tyr15), pCDK1(Thr161), Cyclin B1 (total) and pCyclin B1(Ser126) may be involved in progression of vulvar squamous cell carcinoma. The combination of pCDK1(Thr161), 14-3-3σ, 14-3-3η and Wee1 was a statistically independent prognostic factor.